Gender difference in support for democracy in sub-Saharan Africa: Do social institutions matter? - Maty Konte (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Little investigation has been made to explain why women are less likely than are men to support democracy in sub-Saharan Africa. This gender difference in politics has been found in numerous studies and may hinder the much needed legitimation of democracy in this region. This paper addresses the question of whether this observed gender gap is due to the omission of social institutions related to gender inequality, something that affects women's daily life and deprives them of autonomy at home. We hypothesize that women who live under autocracy at home are less likely to support democracy outside, because it does not affect their private life; this follows the idea that the way women are treated in a society might have major implications for the economic, social, and political functioning of that society. We find that the gender difference in support for democracy is no longer signicant after we control for gender discrimination in the family code, in physical integrity or in civil liberties. This study also provides evidence that women living in countries with favourable laws toward women are more supportive of democracy than women who do not, suggesting that democratic regimes may be more willing than are authoritarian regimes to protect laws friendly to women.
Keywords: J16; O12; O38; O55; 330; support for democracy; gender difference; social institutions